The Influence of Work Environment, Organizational Commitment, Competence and Work Motivation on Employee Satisfaction Mediated by Employee Performance Case Study of Kedungpring Village Office - Tri Septian Anhar; Evi Fitrotun Najiah; Mohammad Yaskun (Jurnal Multidisiplin Sahombu, 2024)
Facing competition in today's era of globalization requires every organization, both in the private and government sectors, to work more efficiently and effectively. Increasingly fierce competition causes organizations to be able to increase competitiveness and dare to face challenges and implications, namely facing changes in achieving the goals and objectives set by the organization. The study used a type of quantitative approach, a sample of 220 based on non-probability sampling techniques with saturated samples, with SEM analysis using the Smart application, PLS version 3.0. With Outer Model Test, Inner Model Test, Mediation Test and Hypothesis Test. The results of the Validity test stated that the Loading Factor number was more than 0.7 and the AVE number was more than 0.5 marked as valid, in the Reliability test the Composite Reliability value and Cronbach's Alpha above 0.7 were marked as reliable. The conclusion obtained is that in the hypothesis submission of the variables of Influence of Work Environment (X1), Organizational Commitment (X2), Competence (X3) and Work Motivation (X4) have a positive and significant effect on Employee Satisfaction (Y), Organizational Commitment (X2), Competence (X3) and Work Motivation (X4) have a positive and insignificant effect on Employee Performance (Z). The mediation test on the variables of Influence of Work Environment (X1), Work Motivation (X4) on Employee Satisfaction (Y) mediated by Employee Performance (Z), said partial mediation. Meanwhile, Organizational Commitment (X2), Competence (X3) to Employee Satisfaction (Y) is mediated by Employee Performance (Z), said to be non-mediated or non-mediated.